Nutritional Status of Patients with Chronic Critical Illness - I. V. Sergeev; M. V. Petrova; A. E. Shestopalov; M. M. Kanarsky; O. B. Lukyanets; I. A. Yarotskaya; Yu. Yu. Nekrasova (Общая реаниматология)
Material and methods. We examined 23 patients with chronic critical illness who were in a minimally conscious state (MCS) with 10.9±2.5 scores on the FOUR (Full Outline of Unresponsiveness) Score Coma Scale. Indicators of carbohydrate, lipid, protein and energy exchange metabolism were evaluated using specimens sampled in the morning hours. Nutritional support was provided by isocaloric isonitrogenic mixtures.Results. Blood biochemistry showed decreases in total protein and albumin levels in 86.9% and 91.3% of patients, respectively. The tests also revealed decreased concentrations of several amino acids, including essential amino acids: histidine (38.3±13.07 µmol/l), methionine (12.68±3.81 µmol/l), threonine (61.6 [58.5;87.7] µmol/l), tryptophan (33.06±15.95 µmol/l), and non-essential amino acids: arginine (40.50 [22.2; 46.9] µmol/l), glutamic acid (124.5±39.29 µmol/l), tyrosine (37.97±10.12 µmol/l). Some correlations between the concentrations of individual amino acids and other indicators were revealed, such as histidine and CRP (r=–0.68, P=0.043), tryptophan and CRP (r=–0.86, P=0.002), histidine and leukocyte count (r=–0.76, P=0.015), methionine and lysine (r=0.88, P=0.008), methionine and patient's weight (r=–0.68, P=0.042). A relationship between threonine concentration and the level of consciousness on the FOUR scale (r=–0.73, P=0.037) was also found. All patients demonstrated significant alterations of carbohydrate and lipid metabolism.Conclusion. Alteration of adequate protein metabolism seems to be the most affected constituent in the nutritional status of patients with chronic critical illness. It is manifested by a decrease in the concentration of total protein and a number of essential and non-essential amino acids, which implies the importance of highprotein nutritional support and correction of the amino acid profile.